SINERGI MULTI PIHAK CSR AQUA KLATEN DALAM UPAYA MELINDUNGI SUMBER MATA AIR SUB DAS PUSUR - Aliefah Rachma Sarwedi; Hari Akbar Sugiantoro (Universitas Muhammadiyah Jember, 2021)
This study aims to analyze the multi-stakeholder synergy of AQUA Klaten's CSR in establishing a rescue program for the Pusur Sub-Regional water flows. This effort requires various parties to collaborate, setting a series of rescue programs from upstream to downstream of the Pusur River. This research was conducted in a qualitative approach through a case study method. The data were obtained from the results of observation, documentation, and interviews through purposive sampling technique. To obtain the final result, the researcher then analyzed the data by using a triangulated analysis of sources. The results of this study indicate that the multi-stakeholder synergy formed an organization called Pusur Institute, which encourage the establishment of integrated series on water sources saving programs. The success of this program depends on the responsibilities of each party. The formation of multi-stakeholder synergies can also reduce conflicts between companies and stakeholders.